Increased volatility of exchange prices on energy resources as an illustration of the new realities of the global economy development in the second decade of the XXI century (World of finance, 2019)
Sokhatska O. Increased volatility of exchange prices on energy resources as an illustration of the new realities of the global economy development in the second decade of the XXI century.Introduction. Increased volatility in the exchange markets of energy resources, primarily oil, is the reality of the global economy development in the second decade of the XXI century. Sharp drops in prices and fast change of trends make these markets difficult to predict, that increases the risks for both producers and consumers, for exporting countries and importers.Purpose. The purpose of the article is the systematization of reasons of increased volatility of energy exchange’s prices primarily oil in the second decade of the XXI century, and development on this basis recommendations for their consideration in the process of reforming energy sector and in determination of controlling parameters in the annual budgets of Ukraine.Results. Global economy restructuring in the context of computerization, robotics and the transition to “clean” types of energy is fait accompli. In implementing the strategy of comprehensive reformation of all spheres of activity in our country, consideration of these trends in global economic development is not only appropriate, but necessary. In this context provided the limitation of resources, there is no doubt concerning their focus on technological and informational innovations. The above-mentioned follows from the direct need for the withdrawal of Ukraine’s economy from the XX century to the XXI century.Conclusions. Increased volatility in the exchange markets of energy resources, primarily oil, is the reality of the global economy development in the second decade of the XXI century. Sharp drops in prices and fast changing of trends make these markets difficult to predict, that increases the risks for both producers and consumers, for exporting countries and importers. Until recently, increased volatility and lack of methods for accurate predictions of future prices of energy markets had been explained by the effect of random factors (natural and manmade disasters, political conflicts and military actions in the area of production) and the presence of significant by volumes speculative component of exchange markets. However, in the post-crisis period more significant factors of influence on hydrocarbon prices in general and oil in particular are clearly manifested, the effect of which is caused by deep structural transformation, serving the global economy. It is about innovative development, including the transition of humanity to the era of the fourth industrial revolution, which involves fundamental changes of forms and types of business in general, and its energy supply in particular